2011
DOI: 10.1074/jbc.m111.257154
|View full text |Cite
|
Sign up to set email alerts
|

Cell Entry of Avian Reovirus Follows a Caveolin-1-mediated and Dynamin-2-dependent Endocytic Pathway That Requires Activation of p38 Mitogen-activated Protein Kinase (MAPK) and Src Signaling Pathways as Well as Microtubules and Small GTPase Rab5 Protein

Abstract: Very little is known about the mechanism of cell entry of avian reovirus (ARV). The aim of this study was to explore the mechanism of ARV entry and subsequent infection. Cholesterol mainly affected the early steps of the ARV life cycle, because the presence of cholesterol before and during viral adsorption greatly blocked ARV infectivity. Although we have demonstrated that ARV facilitating p38 MAPK is beneficial for virus replication, its mechanism remains unknown. Here, we show that ARV-induced phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 66 publications
(79 reference statements)
2
37
0
Order By: Relevance
“…For example, p38 MAPK activation and signaling is important for viral entry of reovirus and respiratory virus (Huang et al, 2011; Marchant et al, 2010). p38 MAPK signaling has also been implicated as playing a role in the viral transcription and translation of a number of viruses including hepatitis C virus, avian reovirus, porcine circovirus type 2, porcine reproductive and respiratory syndrome virus, rotavirus, Kaposi sarcoma-associated herpesvirus, encephalomyocarditis virus and HIV-1 (Cohen et al, 1997; George et al, 2012; Hirasawa et al, 2003; Jafri et al, 2007; Ji et al, 2009; Lee and Lee, 2012; Pan et al, 2006; Wei et al, 2009); and inhibition of p38 MAPK signaling has been shown to directly inhibit virus infection (Chang et al, 2008; Ludwig et al, 2003; Wei et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, p38 MAPK activation and signaling is important for viral entry of reovirus and respiratory virus (Huang et al, 2011; Marchant et al, 2010). p38 MAPK signaling has also been implicated as playing a role in the viral transcription and translation of a number of viruses including hepatitis C virus, avian reovirus, porcine circovirus type 2, porcine reproductive and respiratory syndrome virus, rotavirus, Kaposi sarcoma-associated herpesvirus, encephalomyocarditis virus and HIV-1 (Cohen et al, 1997; George et al, 2012; Hirasawa et al, 2003; Jafri et al, 2007; Ji et al, 2009; Lee and Lee, 2012; Pan et al, 2006; Wei et al, 2009); and inhibition of p38 MAPK signaling has been shown to directly inhibit virus infection (Chang et al, 2008; Ludwig et al, 2003; Wei et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the endosomal pathway has been shown to promote internalization and/or virus replication (60)(61)(62)(63). Indeed, entry into Rab5 ϩ early endosomes has been previously described for Uukuniemi virus, another member of the genus Phlebovirus (64).…”
Section: Sftsv Nss Sequesters Rig-i Signaling Molecules Into Nssinducmentioning
confidence: 99%
“…The σC protein plays a role for virus attachment [16] and as apoptosis inducer [17]. It has been demonstrated that cell entry of avian reovirus follows a caveolin-1-mediated and dynamin-2-dependent endocytic pathways that require activation of p38 MAPK and Src signaling pathways [18]. It has also been suggested that it represents the target for type-specific neutralizing antibodies.…”
Section: Introductionmentioning
confidence: 99%